Optimal Configuration of N‐Doped Carbon Defects in 2D Turbostratic Carbon Nanomesh for Advanced Oxygen Reduction Electrocatalysis. Issue 29 (12th May 2020) - Lai, Qingxue; Zheng, Jing; Tang, Zeming; Bi, Da; Zhao, Jingxiang; Liang, Yanyu
Abstract: The charge redistribution strategy driven by heteroatom doping or defect engineering has been developed as an efficient method to endow inert carbon with significant oxygen reduction reaction (ORR) activity. The synergetic effect between the two approaches is thus expected to be more effective for manipulating the charge distribution of carbon materials for exceptional ORR performance. Herein we report a novel molecular design strategy to achieve a 2D porous turbostratic carbon nanomesh with abundant N‐doped carbon defects (NDC). The molecular level integration of aromatic rings as the carbon source and urea units as the N source and sacrificial template into the novel precursor of polyurea (PU) promises the formation of abundant carbon edge defects and N doping sites. A special active site—a carbon edge defect doped with a graphitic valley N atom—was revealed to be responsible for the exceptional ORR performance of NDC material. Abstract : Defects on purpose : A two‐dimensional porous turbostratic carbon nanomesh with abundant carbon defects coupled with N doping sites was developed by a novel molecular design strategy. This material displays exceptional oxygen reduction reaction electrocatalytic activity, which is attributed to the formation of highly exposed carbon edge defects doped with graphitic valley N atoms.